Determinan Tingkat Pengungkapan Wajib Laporan Keuangan Pemerintah Kabupaten/Kota di Provinsi Sumatera Selatan - Periansya; Desi Indriasari; Putri Laila Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research aims to examine the effects of local government size, intergovernmental revenue, job specialization, and capital expenditure on the level of mandatory financial statement disclosure of local governments. Disclosure is based on Government Regulation related to Government Accounting Standards Number 71 of 2010. Secondary data is sourced from Audit Reports (LHP) on Local Government Financial Statements (LKPD). The sample comprises 17 districts/cities in South Sumatra Province with 51 LKPD audit reports from 2020-2022. Data is analyzed using multiple linear regression techniques with Eviews 12. The study finds that local government size significantly and positively affects the level of mandatory financial statement disclosure; intergovernmental revenue significantly and negatively affects the level of mandatory financial statement disclosure; while job specialization and capital expenditure do not have a significant effect on the level of mandatory financial statement disclosure; and all four factors together significantly affect the level of mandatory financial statement disclosure